2010
DOI: 10.1093/hmg/ddq246
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking the causes of multifactorial disorders: OXPHOS differences between mitochondrial haplogroups

Abstract: Many epidemiologic studies have associated human mitochondrial haplogroups to rare mitochondrial diseases like Leber's hereditary optic neuropathy or to more common age-linked disorders such as Parkinson's disease. However, cellular, biochemical and molecular-genetic evidence that is able to explain these associations is very scarce. The etiology of multifactorial diseases is very difficult to sort out because such diseases are due to a combination of genetic and environmental factors that individually only co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
222
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 245 publications
(239 citation statements)
references
References 57 publications
15
222
2
Order By: Relevance
“…5 This mutation provokes an important decrease in the EFTs levels, but the EFTu amount is not affected (Figure 1d). A mitochondrial protein synthesis analysis 6 also showed an important decrease in the levels of mtDNAencoded polypeptides (Figure 1e). …”
Section: Resultsmentioning
confidence: 91%
“…5 This mutation provokes an important decrease in the EFTs levels, but the EFTu amount is not affected (Figure 1d). A mitochondrial protein synthesis analysis 6 also showed an important decrease in the levels of mtDNAencoded polypeptides (Figure 1e). …”
Section: Resultsmentioning
confidence: 91%
“…mtDNA haplogroups have been shown to modulate the efficiency of adenosine triphosphate synthesis or the production of reactive oxygen species, 26 and these effects could directly modulate neuronal protection rather than damage. It also likely that haplogroups J, T, and K are genetic tags of further mtDNA variation not directly genotyped in this study.…”
mentioning
confidence: 99%
“…Additional haplogroup association studies also conclude that particular mtDNA haplogroups or haplogroup clusters may influence PD risk although risk attributions between the different populations analyzed do vary (5,38,102,151). The question of whether mtDNA haplogroups are functionally relevant has also been raised, and one recent cybrid study did find differences in mitochondrial respiratory capacity in cells containing haplogroup H versus haplogroup Uk (40). Other cybrid studies have similarly reported that common mtDNA polymorphisms may influence mitochondrial function (54,99).…”
Section: Are Specific Mtdna Signatures Typical Of Pd?mentioning
confidence: 99%
“…It increasingly appears these polymorphisms may subtly influence mitochondrial function (40,54,99). This may apply to even extremely common synonymous mtDNA polymorphisms that do not cause amino acid substitutions (70).…”
Section: Are Specific Mtdna Signatures Typical Of Pd?mentioning
confidence: 99%